2017
DOI: 10.1186/s12885-017-3733-3
|View full text |Cite|
|
Sign up to set email alerts
|

Oncology practitioners’ perspectives and practice patterns of post-treatment cancer survivorship care in the Asia-Pacific region: results from the STEP study

Abstract: BackgroundMost efforts to advance cancer survivorship care have occurred in Western countries. There has been limited research towards gaining a comprehensive understanding of survivorship care provision in the Asia-Pacific region. This study aimed to establish the perceptions of responsibility, confidence, and frequency of survivorship care practices of oncology practitioners and examine their perspectives on factors that impede quality survivorship care.MethodsA cross-sectional survey of hospital-based oncol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 13 publications
5
52
0
Order By: Relevance
“…Most studies reported in the 22 articles had a cross‐sectional quantitative (13) or qualitative (6) design, while two used mixed methods (surveys and interviews), and one was longitudinal (surveys and interviews) . Most (19) included physician perspectives as a main outcome measure, although three included physician perspectives as an adjunct to patient perspectives. Some articles were excluded because they focused on nonphysician providers such as nurses, nurse practitioners, physician assistants and allied healthcare providers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies reported in the 22 articles had a cross‐sectional quantitative (13) or qualitative (6) design, while two used mixed methods (surveys and interviews), and one was longitudinal (surveys and interviews) . Most (19) included physician perspectives as a main outcome measure, although three included physician perspectives as an adjunct to patient perspectives. Some articles were excluded because they focused on nonphysician providers such as nurses, nurse practitioners, physician assistants and allied healthcare providers.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies in this review focused on patients with lung cancer, two focused on breast cancer, and the remaining 18 focused on multiple or unspecified types of cancer . Also, studies focused on different phases of cancer care, including those who had completed cancer treatment, were undergoing active cancer treatment or were in varying or unspecified phases of cancer care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that resources are limited in many healthcare systems, we believe it is essential to develop a multidisciplinary, structured approach in treating HNC patients to ensure a comprehensive understanding of their needs. Because health professionals differ in their roles, in the frequency of care after treatment, and employ different care provision standards (Chan et al, 2017), improving communication and coordination between professionals, especially primary care physicians and oncologists (Klabunde et al, 2013), will help ensure optimal follow-up care.…”
Section: Interpersonal Relationshipsmentioning
confidence: 99%
“…[18][19][20] However, the current provision of survivorship care services remained inconsistent and unorganized in the Asia-Pacific region, including high-resource countries like Singapore where services are segregated by cancer types without age specificity. [21][22][23][24][25] As AYA cancer survivors experience a higher psychosocial distress and morbidity burden compared with their cancer-free peers, this segregation would result in services that do not comprehensively and adequately address the unique age-related challenges AYA face. 26 Thus, a change is needed for better management of AYA survivors' needs to improve their quality of life.…”
Section: Introductionmentioning
confidence: 99%